Fabrication of monolithic CZTS/Si tandem cells by development of the intermediate connection. (15th September 2019) - Valentini, Matteo; Malerba, Claudia; Serenelli, Luca; Izzi, Massimo; Salza, Enrico; Tucci, Mario; Mittiga, Alberto
Highlights: A first working monolithic CZTS/Si tandem cell is presented and characterized. A MoS2 /FTO/ZnO intermediate contact between top and bottom cells is developed. Limiting factors of this device are addressed and investigated to overcome them. Abstract: Earth abundant Cu2 ZnSnS4 (CZTS) semiconductor can find a promising application as wide-bandgap top cell absorber in CZTS/Silicon tandem devices. The coupling between the top and the bottom cells in a monolithic device requires the development of a proper intermediate connection able to ensure: (i) high transparency in the infrared region (ii) good electric contacts and (iii) good chemical stability under thermal treatments used for the CZTS growth, in order to prevent elements interdiffusion and silicon degradation. To this purpose, some multilayered structures based on MoS2 and different Transparent Conductive Oxides (TCOs) were tested as intermediate connection in CZTS/Silicon tandem devices. The first working monolithic tandem cell, with open circuit voltage of about 950 mV and an efficiency of 3.5%, was obtained using a MoS2 /FTO/ZnO trilayer structure as intermediate contact between the top and the bottom cells. Some limiting factors of this device were addressed and investigated in order to increase the tandem cell efficiency.